Peculiarities of venous hemodynamics of the brain in children with asthma - S.N. Nedelskaya; E.Yu. Akulova (Zaslavsky O.Yu., 2018)
Background. Data on the number of patients with chronic cerebral ischemia among children and adolescents are single and small. Consequently, the relevance of the study of the state and changes in cerebral hemodynamics, including venous circulation, in children with asthma is beyond doubt and is an extremely acute issue. Materials and methods. Ultrasound dopplerographic examination was performed for 101 children with asthma and 30 healthy children aged 10-17 years to study the peculiarities of venous hemodynamics of the brain. Children with asthma were divided according to gender composition, degree of control and duration of the disease. Results. Ultrasound dopplerography was performed with the determination of the maximum linear velocity of blood flow in the basal vein of Rosenthal. The presence of the phenomena of persistent venous dyshemia and venostasis in children with asthma, especially boys, was established, regardless of the degree of asthma control. The duration of the disease for more than 5 years also had a negative effect on the indices of venous hemodynamics. Conclusions. Features of venous circulation in children with asthma are early preclinical signs of cerebrovascular disorders. It is suggested to include such children to the risk group of cerebrovascular pathology in the future. It is advisable to add the outpatient observation of children with asthma by studying the state of venous hemodynamics using transcranial dopplerography and duplex scanning of the main cerebral vessels, which will ensure early diagnosis of cerebrovascular disorders.